2018
DOI: 10.17576/jsm-2018-4701-17
|View full text |Cite
|
Sign up to set email alerts
|

STK15 Phe31Ile and Val57Ile Polymorphisms Increase the Risk of Gastrointestinal Cancer

Abstract: STK15 is a serine/threonine kinase that regulates chromosomal segregation during mitosis. Single nucleotide polymorphisms (SNPs) in this gene, Phe31Ile (rs2273535) and Val57Ile (rs1047972), are inconsistently associated with gastrointestinal cancer (GIC) across different populations. However, this association is unclear in Malaysian population. Therefore, this study investigated the association of STK15 Phe31Ile and Val57Ile polymorphisms to GIC risk in Malaysia. Genomic DNA was extracted from 185 GIC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…Because Gu et al also found that Aurora-A rs1047972 polymorphism has an increased risk for lung cancer. But our results were different from Lai et al [24] and Bao et al [26], Lai et al found the association of Aurora-A rs1047972 polymorphism with an increased risk of gastric cancer susceptibility in Malaysians, and gastric cancer incidences among Malaysians have significantly association among younger age group (<50 years). Bao et al found AA carriers of the Aurora-A rs1047972 polymorphism were significantly associated with decreased susceptibility to HBV-related hepatocellular carcinoma when compared with non-carriers.…”
Section: Discussioncontrasting
confidence: 99%
“…Because Gu et al also found that Aurora-A rs1047972 polymorphism has an increased risk for lung cancer. But our results were different from Lai et al [24] and Bao et al [26], Lai et al found the association of Aurora-A rs1047972 polymorphism with an increased risk of gastric cancer susceptibility in Malaysians, and gastric cancer incidences among Malaysians have significantly association among younger age group (<50 years). Bao et al found AA carriers of the Aurora-A rs1047972 polymorphism were significantly associated with decreased susceptibility to HBV-related hepatocellular carcinoma when compared with non-carriers.…”
Section: Discussioncontrasting
confidence: 99%